(untitled) - Haslach, Henry W. (New York, 2003)
Text presents a quantitative description of the mechanical behavior of a broad range of deformable bodies under widely differing conditions, and introduces the key tools needed to avoid material functional behavior. For upper-level undergraduate students and graduate students. Includes index, references, appendix, and chapter problems.
Keywords: Deformations ( Mechanics ),Materials; Mechanical properties